Walking in My Shoes: How Expectations of Role Reversal in Future Negotiations Affect Present Behaviors. (June 2016) - Bagchi, Rajesh; Koukova, Nevena T.; Gurnani, Haresh; Nagarajan, Mahesh; Oza, Shweta S.
The authors focus on repeated distributive negotiations to investigate how expectations of role reversal in future transactions (i.e., a buyer [seller] in one transaction is the seller [buyer] in the next transaction) affect behaviors in the current negotiation. They demonstrate that when negotiators expect a role reversal, they are likely to make more concessions and reach agreement more quickly in the current negotiation. The authors find that this effect is driven by negotiators' beliefs that they will be able to recover these concessions, because negotiators expect their counterparts to reciprocate in the later transaction when the parties reverse roles. However, when the two negotiations occur in different "accounting" periods (i.e., fiscal periods) or when the negotiating parties do not explicitly communicate their willingness to reverse roles in the future, role-reversal expectations do not affect concession making. Implications arise in both managerial and consumer contexts where the possibility of engaging in future negotiations—as well as reversing roles—exists.